1991
DOI: 10.1023/a:1015816825920
|View full text |Cite
|
Sign up to set email alerts
|

Untitled

Abstract: We describe a simplified and rapid liquid chromatographic determination of antipyrine clearance (CLAP) calculated from peak height ratios of drug/internal standard. Saliva or plasma was collected 24 hr after the oral administration of 1 g of antipyrine to the subject. A 25-microliter aliquot of the sample is deproteinized with acetonitrile containing 3-nitrophenol (internal standard) and injected into a radial compression module equipped with a 10-micron, 8 mm x 10-cm C18 cartridge, using a 0.025 M aqueous sol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1993
1993
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(2 citation statements)
references
References 16 publications
0
2
0
Order By: Relevance
“…The aminopyrine content (g per tablet, g mL À1 ) in the samples were also determined by HPLC according to a previously reported method. 33 The results are also listed in Table 2. There was no significant difference between the results obtained by the HPLC method and Bi 2 S 3 / GCE.…”
Section: Analytical Applicationmentioning
confidence: 99%
“…The aminopyrine content (g per tablet, g mL À1 ) in the samples were also determined by HPLC according to a previously reported method. 33 The results are also listed in Table 2. There was no significant difference between the results obtained by the HPLC method and Bi 2 S 3 / GCE.…”
Section: Analytical Applicationmentioning
confidence: 99%
“…Several research studies have revealed that there is a direct association of macro and trace elements with diabetes mellitus [6]. Diabetes mellitus has been found to be associated with abnormalities in the metabolism of some of the elements such as Cu, Zn, Fe, Se, Mg, Cr, V, Ca and K [7,8]. Leptadenia hastata (Pers) Decne (Family-Asclepiadaceae), commonly known as yadiya is an edible nondomesticated vegetable collected in wild throughout Africa.…”
Section: Introductionmentioning
confidence: 99%